Pengaruh Ekstrakurikuler Pramuka dalam Mengembangkan Karakter Jujur dan Disiplin pada Siswa MTsN 1 Kota Payakumbuh - Mosnadia, Mosnadia; Santosa, Budi (Lembaga Yasin AlSys, 2023)
The problem that occurs in students is the lack of self-discipline and honesty. The aim of the study was to see how much influence scout extracurriculars had in developing honest and disciplined characters in students at MTsN 1 Payakumbuh City. The quantitative research method is a regression type. The population in this study were 320 students of class VIII MTsN 1 Payakumbuh. The sample in this study were 70 people. In taking samples, the authors use random sampling technique. Random sampling technique is a sampling technique in which the population is randomized. Data was collected using a questionnaire instrument with a Likert scale type. Data analysis techniques used the normality test, linearity test, and hypothesis testing using the Wilcoxon test, correlation test using the Spearmen rho test with the help of the SPSS 25 application. There were 70 positive data (N) meaning there was an increase, the mean of rank was 35.50 while the sum of rank of 2485.00 is 0 so that it can be said that there is no equal value between X and Y1. From the explanation above it can be said that there is an honest increase, there are 70 positive data (N) meaning there is an increase, the mean of rank is 35.50 while the sum of rank is 2485.00 is 0 so it can be said that there are no equal values between. From the explanation above it can be said that there is an increase in discipline. the Wilcoxon test was carried out to find out the value obtained by a significance value of p-value of 0.000. Based on the applicable provisions, it is known that the results of the Wilcoxon Sig. p-value 0.000 <α (α =0.05) which means that Ha is accepted. Based on the results of the Wilcoxon test above, it can be concluded that Ha is accepted with the proposed hypothesis.